Bounds On Fuzzy Dominator Chromatic Number of Fuzzy Soft Bipartite Graphs - Jahir Hussain R; Afya Farhana M (Ratio Mathematica, 2023)
An FSG GS(T,V) fuzzy’s soft dominator colouring (FSDC) is a suitable Fuzzy Soft Colouring (FSC) where every node of a colour group is dominated by a vertex of GS(T,V). In the current work, we characterize the sharp bounds for the Fuzzy Dominator Chromatic Number (FDCN) of fuzzy soft bipartite graphs and we present limits on the FDCN of fuzzy soft bipartite graph in terms of the γe(GS(T; V )). Furthermore, we classify fuzzy soft bipartite graphs into three classes based on FDCN